Product development using banner canvas: experience of an extension project in Northwest Parana (Research, Society and Development, 2021)
The wide use of polyvinyl chloride (PVC) for the production of the most diverse types of products due to its versatility and low cost, makes this material one of the most used by industries, but on the other hand it generates a significant environmental impact, whether during their production and mainly in the disposal. The vinyl canvas used for congress and advertising banners, which are normally used for very short periods, are made of PVC and other components, which makes it difficult to recycle. Furthermore, when they are discarded in landfills, they take years to decompose. In view of the need to find sustainable alternatives, this article aims to reuse banner tarps for the construction of bags and accessories through extension courses offered to communities in the northwest of Paraná, aiming at increasing the life cycle of this material made from PVC. The main results obtained showed the viability of producing the artifacts using the banners used as the main raw material. Finally, it was concluded that at the same time that the project contributed to reducing the environmental impact of the disposal of the material, on the other hand it contributed as another income alternative for craftsman.